Lung Cancer Surgery Part G: Superior Sulcus Tumours - (:unkn) unknown (BENTHAM SCIENCE PUBL, 2013)
Superior sulcus tumours were first described by a radiologist Henry Pancoast. These rare tumours have typical presentation as causing Pancoast-Tobias syndrome. The management and outcome of superior sulcus tumours remained nearly unchanged in the last 40 years. Patients with, extrathoracic metastases, proven N2 disease, invasion of the superior and middle trunk of the brachial plexus, spinal canal, esophagus and trachea are not suitable for resection. All the diagnosed patients who do not have absolute contraindications for surgery should be evaluated for combined therapy including surgical excision. In this chapter, we discussed the superior sulcus tumours with diagnosis, treatment and results with the current literature.
Keywords: Superior sulcus tumours; pancoast; surgery; SURGICAL RESECTION; BRACHYTHERAPY; PULMONARY; SURVIVAL